Using Motivational Expressions as Reinforcement to Boost Learners’ Learning of English at Primary School Level Case of 3rd Year Pupils at Aouidjia Abdallah Ben Tayeb Primary School in Souk-Ahras - GUITOUNI Wissal (My University, 2023)
Abstract The aim of this study is to probe the use of motivational expressions as a form of reinforcement to boost learners’ learning of the English language at the primary Level in Aouidjia Abdallah Ben Tayeb primary school in Souk-Ahras. Our research utilised a qualitative data method. Initially, a participant observation was realised. Secondly, a quasi-experiment was conducted with a group of 37 third year primary school learners as an experimental group. Thirdly, an interview was conducted with one EFL teacher in the aforementioned institution. The obtained findings unveiled that using motivational expressions has a positive impact on learners, they created a supportive and positive learning environment which made pupils feel more comfortable and engaged in the learning process. Based on these findings, our hypothesis is confirmed. Consequently, using spesific motivational expressions as a form of reinforcement in primary schools is recommended to promote positive behaviours and attitudes in the classroom and make learners more interested and engaged to learn the English language. ----------------------- ملخص تهدف هذه الدراسة إلى التحقيق في استخدام التعبيرات التحفيزية لتعزيز تعلم التلاميذ في المدرسة الابتدائية عوايجية عبد الله بن الطيب ، في سوق أهراس. التعبيرات التحفيزية إيجابية وتهدف إلى تشجيع المتعلمين على الانخراط في السلوكيات الإيجابية. استخدم هذا البحث الكيفي لجمع البيانات ثلاث أدوات رئيسية. في البداية، تم إجراء ملاحظة بالمشاركة على مدار ست حصص، كما تم إجراء تجربة مع 37 طالبً في السنة الثالثة ابتداىي ومقابلة مع استاذة اللغة الإنجليزية كلغة أجنبية. أظهرت النتائج التي تم الحصول عليها أن استخدام التعبير التحفيزي له تأثير كبير على المتعلمين ، فهم يخلقون بيئة تعليمية داعمة وإيجابية، مما يجعلهم يشعرون بمزيد من الراحة والمشاركة في عملية التعلم. بناءً على هذه النتائج، تم تأكيد الفرضية. وبالتالي ، يوصى باستخدام التعبيرات التحفيزية في المدرسة الابتدائية لزيادة مشاركة الطلاب. بشكل عام،كما تسلط الضوءعلى أهمية استخدام التعبيرات التحفيزية لتعزيز السلوكيات والمواقف الإيجابية في الفصل الدراسي. --------------------------- Résumé L'objectif de cette étude est d'examiner l'utilisation d'expressions motivantes comme forme de renforcement pour stimuler l'apprentissage de la langue anglaise au niveau primaire à l'école primaire Aouidjia Abdallah Ben Tayeb à Souk-Ahras. Notre recherche a utilisé une méthode de données qualitatives. Dans un premier temps, une observation participante a été réalisée. Deuxièmement, une quasi-expérience a été menée avec un groupe de 37 apprenants de troisième année d'école primaire comme groupe expérimental. Troisièmement, un entretien a été mené avec un enseignant d'anglais langue étrangère dans l'institution susmentionnée. Les résultats obtenus ont révélé que l'utilisation d'expressions motivantes a un impact positif sur les apprenants, elles créent un environnement d'apprentissage positif et favorable qui permet aux élèves de se sentir plus à l'aise et de s'engager dans le processus d'apprentissage. Sur la base de ces résultats, notre hypothèse est confirmée. Par conséquent, il est recommandé d'utiliser des expressions motivationnelles spécifiques comme forme de renforcement dans les écoles primaires afin de promouvoir des comportements et des attitudes positifs en classe et de rendre les apprenants plus intéressés et engagés dans l'apprentissage de la langue anglaise.